Resilience Of Children's Language Acquisition In Intact Families In Bangkalan: A Psycholinguistic Study - Antono Mixghan Norman; Hani’ah Hani’ah; Faisal Faisal (SHS Web of Conferences)
This study aims to describe and elaborate family problems and aspects of resilience reflected in children with an intact family background. The research method used in this study is a qualitative research design of case study type. The location of data collection in this study is located in Bangkalan Regency. The form of data in this study is in the form of verbal utterances regarding resilience or the acceptance process. The data source in this study uses primary data or data obtained directly from participants as children with an intact family background. The analysis of the resilience factors of the three research subjects refers to the theory of resilience by Reivitch and Sahtee, which includes emotion regulation, empathy, reaching out, impulse control, self-efficacy, optimism, and problem cause analysis. The results of this study indicate that of the three research subjects, subjects 1, 2, and 3 have the same family problems, namely victims of parental divorce, and have ways to rise from adversity that are similar at first glance, although there are visible differences. It is hoped that this research can provide additional references and insights into resilience in a person.